Analysis of Ability to Recognize Letters B and D Ages 5 — 6 Years in Private Kindergarten St. Antonius 2 Medan - Janetria (PT FORMOSA CENDEKIA GLOBAL, 2024)
The problem in this study is that some children are not able to correctly name letter symbols such as the letter “b” to “d”. This study aims to determine the analysis of children's ability to recognize the letters b and d by writing to the board and mentioning the letters b and d. The study is a type of qualitative descriptive research. The subjects of the study were 5 children who knew letters b and d in class B1 in kindergarten St. Antonius 2 Medan. To obtain data using observations and documentation. Data already collected are analyzed, data reduction, as well as data presentation and conclusion drawing. The results of the study at St. Antonius Kindergarten 2 Medan showed that an analysis of the ability to recognize letters b and d was carried out to the respondents with assessment indicators that the researcher had provided through observation methods. Respondents A, B, C and D at the time of the ability to recognize the letters b and d arose awareness of the letters b and d by being marked while learning to the blackboard. Stages of writing the letters b and d on the board, respondents A, B, C, and D were already able to give meaning to the vision on the board letters b and d by using good language.